2008
DOI: 10.1002/app.28537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silica‐based nanofillers on the properties of a low‐density polyethylene/ethylene vinyl acetate copolymer based thermoplastic elastomer

Abstract: The effect of pristine silica nanoparticles on a model low-density polyethylene (LDPE)-ethylene vinyl acetate copolymer (EVA) thermoplastic elastomer blend system is explored in this article. Pristine silica nanoparticles were melt-blended with the LDPE-EVA system at 1.5, 3, and 5 wt % loadings through the variation of the sequence of addition. In one of the compositions, coupling agent bis [3-(triethoxysilyl)propyl] tetrasulfide (Si-69) was used to improve the interaction of hydrophilic silica fillers with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 60 publications
4
39
0
Order By: Relevance
“…15 In all the compositions, EVA domains have been found to exist as dispersed phase in the continuous matrix. 17 However, it has been found that in CS/3-1, in the continuous phase, due to intermixing of EVA and LDPE silica particles remained associated in both phases as well as in the interface. This intermixing phenomenon has been proven by extensive FTIR and TEM analysis in one of our recent publications.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…15 In all the compositions, EVA domains have been found to exist as dispersed phase in the continuous matrix. 17 However, it has been found that in CS/3-1, in the continuous phase, due to intermixing of EVA and LDPE silica particles remained associated in both phases as well as in the interface. This intermixing phenomenon has been proven by extensive FTIR and TEM analysis in one of our recent publications.…”
Section: Resultsmentioning
confidence: 98%
“…15 Because of intermixing, crystallinity of LDPE matrix was reduced. 17 On the contrary, for CS/3-2 no such intermixing was found as the silica-EVA masterbatch was prepared previously before mixing them with LDPE. Here, silica particles were mostly found to be associated with the EVA domains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical and dielectric properties of PVDF/ MWCNTs nanocomposites were improved with PU addition (77). The addition of a silane coupling agent to nano silicafilled LDPE/EVA thermoplastic elastomer polymer blends leads to significant increases in the tensile strength, Young's modulus, extensibility and dynamic properties (78).…”
Section: Thermoplastic-elastomer Polymer Blend Nanocompositesmentioning
confidence: 99%
“…1 Linear low-density polyethylene (LLDPE)/ethylene vinyl acetate copolymer (EVA) blends are used extensively in many applications such as wire and cable coating industry as insulation or jacket, shrinkable films, and multilayer packaging. The polymer blending is one of the economical and easy routes for developing new materials with novel properties.…”
Section: Introductionmentioning
confidence: 99%